XS3: a system for similarity evaluation in multimedia-based heterogeneous XML repositories - Tekli, Joe (2008)
Just as in the real world, plants are important objects in virtual world for creating pleasant and realistic environments, especially those involving natural scenes. As such, much effort has been made in realistic modeling of plants. As the trend moves ...